Beyond facilitator? State roles in global value chains and global production networks. Issue 2 (February 2017) - Horner, Rory
Abstract: Designed to break with state‐centric approaches to understanding economic development, global commodity chain, global value chain (GVC), and global production network (GPN) analyses have deepened our understanding of the corporate governance of global lead firms and associated development outcomes in an era of globalisation. Although this research field is recognised to have provided considerable insight into private governance, a rapidly emerging body of research has given greater attention to the role of the state in GVCs and GPN. Although the state playing a role as facilitator towards firms participating in GPNs has often been an emphasis, this article argues that a variety of other roles are of increasing prominence, including as regulator, producer (state‐owned enterprises), and buyer (public procurement). A major challenge for both policymakers and researchers is to understand how a range of state initiatives not just shape but also are shaped by their positioning in GVCs and GPNs.